2001
DOI: 10.1128/jb.183.18.5248-5256.2001
|View full text |Cite
|
Sign up to set email alerts
|

Catabolite Repression of the Citrate Fermentation Genes in Klebsiella pneumoniae : Evidence for Involvement of the Cyclic AMP Receptor Protein

Abstract: Klebsiella pneumoniae is able to grow anaerobically with citrate as a sole carbon and energy source by a fermentative pathway involving the Na ؉ -dependent citrate carrier CitS, citrate lyase, and oxaloacetate decarboxylase. The corresponding genes are organized in the divergent citC and citS operons, whose expression is strictly dependent on the citrate-sensing CitA-CitB two-component system. Evidence is provided here that the citrate fermentation genes are subject to catabolite repression, since anaerobic cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…We postulate that G3P inhibits EIIA Glc -P-mediated stimulation of adenylate cyclase, thus lowering the cAMP concentration. A recent publication described the catabolite repression of citrate fermentation genes in Klebsiella pneumoniae by glycerol and gluconate, among other compounds (25). The authors of that report also noted the discrepancy between the state of dephosphorylation of EIIA Glc and the repressing effect of non-PTS sugars while maintaining the importance of the cAMP-CAP system in this type of catabolite repression.…”
Section: Discussionmentioning
confidence: 83%
“…We postulate that G3P inhibits EIIA Glc -P-mediated stimulation of adenylate cyclase, thus lowering the cAMP concentration. A recent publication described the catabolite repression of citrate fermentation genes in Klebsiella pneumoniae by glycerol and gluconate, among other compounds (25). The authors of that report also noted the discrepancy between the state of dephosphorylation of EIIA Glc and the repressing effect of non-PTS sugars while maintaining the importance of the cAMP-CAP system in this type of catabolite repression.…”
Section: Discussionmentioning
confidence: 83%
“…This enzyme has been studied mainly in Klebsiella pneumoniae, where it participates in citrate fermentation under anaerobic conditions. Expression of the oxaloacetate decarboxylase in K. pneumoniae is subject to catabolite repression by the CRP protein (22). A protein showing high similarity to E. coli and K. pneumoniae CRP is present in P. aeruginosa and in P. putida and has been called Vfr (1).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of this adaptive response in K. pneumoniae (4)(5)(6)16), B. subtilis (22,23), and W. paramesenteroides (14 and this work) have shown that the expression of the proteins required for the transport and degradation of citrate is regulated at the transcriptional level. To date, K. pneumoniae CitA, B. subtilis CitT, and W. paramesenteroides CitI have been identified as transcription factors specifically involved in citrate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…This system regulates the expression of two operons, citCDEFG and CitS-oadGAB-citAB, which are involved in the transport and metabolism of citrate. Expression of these operons is induced under anoxic conditions in the presence of citrate and is subject to catabolic repression (6,16). In Bacillus subtilis, the CitS/T two-component system (a member of the CitA/B family) is involved in the regulation of the expression of genes encoding citrate transporters required for the utilization of citrate in aerobic conditions (22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation